Estudo sobre a percepção dos servidores sobre a comunicação organizacional do CESNORS - Fabrizio, Silvane Brand (2016)
This study aims to analyse public servers' perceptions in a public federal institution of higher education, more especifically regarding the organizational communication. In this perspective, there is the case of the Centro de Educação Superior Norte - RS (CESNORS), in English, Superior North Education Center, belonging to the Federal University of Santa Maria, in the city of Frederico Westphalen RS, which develops a variety of communication actions and services, through the Communication Assistance Project , directed to both the internal and external public. Bearing that in mind, the research method was organized into two phases. The first phase followed a quantitative approach, and its objective was to identify the servers' perceptions. The obtained data was analysed through descriptive statistics. In this phase, it was identified the servers' profiles and perceptions in relation to the internal communication, concerning the variables of quality, production, dissemination, transparency, objectivity, efficacy and fluidity. In the second phase, an exploratory qualitative approach was used, based on empirical research. Besides that, as a secondary data source, a documental analysis called Organizational Processes Structure Analysis (RTA) was used, derived from the Planning Administration Office (Pró-reitoria de Planejamento - PROPLAN), related to the Communication Assistance Office, allied to the Dimension 4 - Communication with the society , in relation to the quality references, being that showed in the results discussion. Therefore, through the indicators found in this study, it was possible to elaborate a proposal to improve the organizational communication at the institution, considering it as a tool for strategic planning. The results show, in general, the perception of the servers on organizational communication is positive and deserves continuous improvement in the development and / or maintenance of communication strategies. It is expected that this study will serve as a reflection for the realization of a more effective and transparent communication, in favor of the institutional organization.